Quantification of injury burden and barriers in maintaining quality data. (20th October 2021) - Haagsma, J
Abstract: For policy-makers, quantification of the burden of injury and the determination of the relative attributes of avoidable risk factors to this burden are vital tools for priority-setting purposes. This is particularly important in the case of a rapidly changing injury landscape due to effects of the COVID-19 pandemic. Following the 1996 Global Burden of Disease study the disability adjusted life year (DALY) is widely used to assess the burden of injury. The DALY is a population health metric that expresses health loss due mortality, morbidity and disability into a single number. This allows comparisons of distinct health outcomes across subgroups of a population and over time. In addition, cost-of-illness studies can be used to assess the societal burden of injury. Cost-of-illness studies may vary with regards to the time horizon that is used as well as the cost components, which may include intramural and extramural costs as well as productivity loss due work absenteeism due to injury. Essential for the calculation of injury DALYs and cost-of-illness is relevant data on the occurrence of injury, injury deaths, data on exposure to risk factors for injuries, health care consumption and return to work. However, each phase of the pandemic posed different barriers maintaining collection of quality data which may subsequently jeopardize accurate injury DALY calculations and determination of the relative attributes of avoidable risk factors during the COVID-19 pandemic.